The Padlet Media Design Based on Bima Local Literature to Improve Student Writing Skills - Arwan; Suryaningsih, Sri (Paedagogia: Jurnal Pendidikan, 2024)
This research aims to improve students' writing skills through the use of Padlet media which is integrated with local wisdom of Bima regional literature. The background of this research is based on the low writing ability of students caused by monotonous traditional learning methods and the lack of use of interactive media. This research uses the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. Local literature, such as folklore and poetry, is integrated into Padlet's platform as teaching materials to provide relevant cultural context for students. The participants in this study are 30 students of the Indonesian Language and Literature Education Study Program at STKIP Harapan Bima. The results of the study showed a significant improvement in students' writing skills after the use of Padlet based on local wisdom. The average writing score of students increased by 25%, especially in the aspects of cohesion, coherence, and idea development. In addition, students also reported increased motivation and active involvement in writing learning through Padlet's collaborative features, such as writing sharing and feedback. However, there are several technical obstacles faced, such as limited internet access and lack of digital literacy among students. The results of this study have implications that the integration of digital technology and local wisdom can be an innovative strategy in improving students' writing skills, as well as fostering their cultural awareness.